Finite element and experimental validation of sample size correction factors for indentation on asphalt bitumens with cylindrical geometry. (8th March 2021) - Cárdenas, Manuel; Filonzi, Angelo; Delgadillo, Rodrigo
Highlights: FE simulations are used to calculate size effects for cylindrical indentation on asphalt bitumens. Comparisons are made with analytical solutions available in the literature. Effect of finite depth on indentation matched for both solutions, FE and analytical. Effect of lateral confinement calculated using FE is greater than the one obtained analytically. Creep compliances from corrected indentations agreed with creep compliances from DSR. Abstract: Characterization of asphalt bitumens by indentation has been traditionally carried out neglecting the effect of boundary conditions. Recent theoretical and experimental works demonstrated that the effect of sample size on indentation of asphalt bitumens can be significant. In this paper, sample size correction factors for indentation with cylindrical geometry are obtained using finite element simulations. The correction factors calculated for finite sample depth matched the ones obtained analytically in previous research. The adjustment factors for finite lateral dimensions obtained through finite element were, however, significantly higher than the previously obtained by analytical means. The main reason for the difference is that the volumetric effects captured by the finite element analysis were neglected in the previous analytical approach. Additionally, indentation testing was carried out on an unmodified asphalt bitumen using nine different sample sizes. The raw indentations measured on the different sample sizes varied significantly among each other. When the indentations were corrected for sample size, the adjusted results from all samples were considerably similar to each other, indicating that the correction factors accounted properly for the sample size effects on indentations. Creep compliances in shear were obtained from the indentations corrected for sample size. The results matched the creep compliance measured using a dynamic shear rheometer (DSR). On the contrary, the creep compliances obtained from the raw indentations were less than half the magnitude of the creep compliance measured with the DSR. These results confirm the significance of the sample size effects on asphalt bitumen indentation. They also validate the sample size correction factors obtained for indentation of asphalt bitumens with cylindrical geometry.